2016
DOI: 10.9721/kjfst.2016.48.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Traditional Korean Unifloral Honey Based on the Mono-, Di-, and Trisaccharides

Abstract: Sugar profiles of 45 Korean honey samples (15 acacia, 15 multi-floral, 10 chestnut, and 5 artificial honey samples), which are commercially available in the Korean markets, were analyzed using gas chromatography/mass spectrometry (GC/MS) through TMS-oxime and TMS-methoxime derivatization. The average invert sugar contents in acacia, multi-floral, chestnut, and artificial honey samples were 71.2±1.05, 68.7±3.26, 63.2±1.85, and 68.0±2.10%, respectively. Fourteen disaccharides were detected from the samples, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Including also 11 unknown sugars, these authors suggested characteristic sets as identity cards for the Italian honeys: acacia (sucrose, turanose, fructose), chestnut (nigerose, kojibiose, raffinose, isomaltose, isomaltotriose, gentiobiose), rhododendron (melezitose, α-glucose, maltose, erlose, kestose), multifloral (β-glucose), and mountain (melezitose, α-glucose). Jang et al (2016) studied 23 sugars (16 disaccharides and 8 trisaccharides) in Korean acacia, chestnut, multifloral, and artificial honey. Raffinose was more frequent and abundant in chestnut honey (0.01–0.17) mg/100 g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Including also 11 unknown sugars, these authors suggested characteristic sets as identity cards for the Italian honeys: acacia (sucrose, turanose, fructose), chestnut (nigerose, kojibiose, raffinose, isomaltose, isomaltotriose, gentiobiose), rhododendron (melezitose, α-glucose, maltose, erlose, kestose), multifloral (β-glucose), and mountain (melezitose, α-glucose). Jang et al (2016) studied 23 sugars (16 disaccharides and 8 trisaccharides) in Korean acacia, chestnut, multifloral, and artificial honey. Raffinose was more frequent and abundant in chestnut honey (0.01–0.17) mg/100 g.…”
Section: Resultsmentioning
confidence: 99%
“…7 B). However, raffinose also was in the sugar spectra (0.01–0.17 g/100 g) of A. mellifera honey from Korea ( Jang et al, 2016 ), (0.03–0.08 g/100 g) from Spain ( Pascual-Matéa et al, 2018 ), and (0.65 g/100 g) of M. ferruginea from Tanzania ( Popova et al, 2021 ). Therefore, it was not an entomological marker specific for Geotrigona , but it was a discriminant sugar compared to Melipona and Scaptotrigona honeys from Ecuador in this study.…”
Section: Resultsmentioning
confidence: 99%
“…(See Figure 1B). However, raffinose also was in the sugar spectra (0.01-0.17 g/100 g) of A. mellifera honey from Korea (Jang et al, 2016), (0.03-0.08 g/100 g) from Spain (Pascual-Matéa et al, 2018), and (0.65 g/100 g) of M. ferruginea from Tanzania (Popova et al, 2021). Therefore, it is not an entomological marker specific for Geotrigona , but it was a discriminant sugar compared to Melipona and Scaptotrigona honeys from Ecuador in this study.…”
Section: Resultsmentioning
confidence: 99%